A new approach to predict shale gas decline trends in unconventional reservoirs using molecular weight fractionation - Davey,R; Smalley,C; Sephton,M (2018)
© 2018 Society of Petroleum Engineers. All rights reserved. Various aspects of the exploitation of shale reservoirs, whether for hydrocarbon extraction or carbon storage, depend strongly on understanding how the gas is situated at a pore scale within the shale: for example in (isolated) macro-micropores, adsorbed onto the surfaces of pores or absorbed into the matrix of solid shale components. We are testing the hypothesis that gas compositional fractionation during depressurization can be used as a marker for gas stored in these different sites within the shale. This identifies how gas is stored within shales, total gas initially in place (GIP) and location on the estimated ultimate recovery curve (EUR). We created a purpose built sample cell coupled with a GC-FID in order to isolate individual shale constituents and measure molecular weight fractionation between shale gas components from 100% total GIIP to gas depleted. Effects of shale mineralogy on molecular weight fractionation were explored using samples representing key shale constituents as well as “real” shale samples.